(3GdGKfG YTQjI aj GdUdGIs - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj habfG ddGgJOGA HTQjYI CTQa GdeQSdjf (B... (3gPg ebGdI dWjaI aj hGLHGJ GdUdGI GdjhejI heSJMHGJgG eQJHI GdaUhd hGdCHhGH Ydi fgL bQjHs
(3BNQgG (B:s
(3BNQgG(B: (3hQHeG aSQ HCf jLdS Ydi bOejg hjUjH GdCQV HjOg hJQc GdLdhS YdjgG MGd GdJTgO hgh ef GdJQhc GdeDcOI dfgj CHj LYaQ GdHGbQ Yfg aj UMjMg (B... (3Hbhdg(B: (3hEjGc hGdbYhO Ydi bOejc aJJCPi HPdc hdG Jchf bGYOG Ydi GdCQV aJchf EfeG bYO HYVc Ydi HYV adG JHUQ GdJTgO hs
(3JGQjN GdJCdja(B: 1012(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B1: 82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis